Acute Sigmoid Volvulus: Outcome of Primary Resection & Anastomosis in a Tertiary Hospital - Paul, Shantona Rani; Ali, Md Nowshad; Shahid, SM Ahsan; Paul, Subal C; Haque, Md Najmul; Hossain, Md Zamil (TAJ: Journal of Teachers Association, 2023)
Background: Sigmoid volvulus occurs when the sigmoid colon twists on its mesentery and is a cause of intestinal obstruction. Method: This was a descriptive study conducted at the Surgery department of Rajshahi Medical College Hospital during the period from May 2009 to June 2011. Ethical consideration was taken from all the patients. The sample size was 50 with acute sigmoid volvulus. Data were processed and analyzed through SPSS (Statistical package for social sciences). A value of p ≤0.05 was considered significant statistically. Result: Most patients (56%) were diagnosed with acute sigmoid volvulus from the age range of 51-60, among whom male patients had a prevalence (92%). Most of them (92%) were economically impoverished. 36% of patients came to the hospital for treatment from 37-48 hours of illness. The post-operative complication was mild due to wound infection in 10% of patients. Hospital stay was 8-10 days for 76% of patients without complications postoperatively and 11-13 days for 14% of patients. Severe complication Resulting in hospital stay was seen in 4% of patients. Conclusion: Emergency resection of the sigmoid colon and anastomosis in unprepared bowel was an attractive and preferred option in a setting where patients are poor, hospital care often unaffordable and hospital beds are few. TAJ 2022; 35: No-2: 13-18